Measuring the availability of award winning titles in Public Libraries - Ahmad Nadzri Mohamad; Mohd Sharif Mohd Saad; Fuziah Mohd Nadzar (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2013)
This study evaluates the completeness of award winning titles in public library holdings. Three book awards were selected as authoritative lists: (i) National Book Award, (ii) National Prime Literary Award and (iii) National Library Book Award. Three Public Library Corporations were chosen namely Selangor (PPAS), Terengganu (PPNT) and Pahang (PPAP) Public Library Corporations. The objectives of the study were threefold: (i) to identify the availability of award winning books (ii) to identify the completeness of winning titles in each award and (iii) To identify books with the highest number of copies in public library corporations. An inductive checklist evaluation method was used. Collectively, it was found that PPAS has the highest number of copies, i.e. 66.4% (2450 books), followed by PPNT, 30.2% (1115 books) and PPAP with 3.4% (124 books). The public library corporation with the most complete collection is PPAS at 42.8% (62 titles), followed by PPNT at 33.1% (48 titles) and PPAP at 24.1% (35 titles). Award winning titles with the highest number of copies was listed accordingly. This study is imperative to determine the awareness of public libraries in selecting award winning titles as a part of their collection.